Survivors Perceptions of Recovery following Air Medical Transport Accidents. (1st January 2015) - Jaynes, Cathy L.; Valdez, Anna; Hamilton, Megan; Haugen, Krista; Henry, Colin; Jones, Pat; Werman, Howard A.; White, Lynn J.
Abstract Objective: Air medical transport (AMT) teams play an essential role in the care of the critically ill and injured. Their work, however, is not without risk. Since the inception of the industry numerous AMT accidents have been reported. The objective of this research is to gain a better understanding of the post-accident sequelae for professionals who have survived AMT accidents. The hope is that this understanding will empower the industry to better support survivors and plan for the contingencies of post-accident recovery. Methods: Qualitative methods were used to explore the experience of flight crew members who have survived an AMT accident. "Accident" was defined using criteria established by the National Transportation Safety Board. Traditional focus group methodology explored the survivors' experiences following the accident. Results: Seven survivors participated in the focus group. Content analysis revealed themes in four major domains that described the experience of survivors: Physical, Psychological, Relational and Financial. Across the themes survivors reported that industry and company response varied greatly, ranging from generous support, understanding and action to make safety improvements, to little response or action and lack of attention to survivor needs. Conclusion: Planning for AMT post-accident response was identified to be lacking in scope and quality. More focused efforts are needed to assist and support the survivors as they regain both their personal and professional lives following the accident. This planning should include all stakeholders in safe transport; the individual crewmember, air medical transport companies, and the industry at large.